Histoplasmosis presenting as a mediastinal mass - Elise D. Martin; Randi L. Lassiter; Robyn M. Hatley; Kenneth C. Walters (Elsevier, 2018)
Pulmonary histoplasmosis is caused by infection with Histoplasma capsulatum, resulting in a variety of clinical manifestations. We describe a case of an asymptomatic mediastinal mass and calcified pulmonary nodules discovered in immunocompetent child from the Southeastern United States. In the setting of inconclusive noninvasive diagnostic tests and the inability to completely exclude malignancy, the patient was taken to the operating room for excisional biopsy of the mass and right upper lobe lung nodules. A diagnosis of histoplasmosis with mediastinal granulomas was established. The patient was subsequently treated with itraconazole. This article underscores the importance of including endemic mycoses in the differential for mediastinal mass and discusses the utility of surgical intervention for the diagnosis and treatment of histoplasmosis. Keywords: Histoplasmosis, Mediastinal mass, Cryptococcus